Water Movement in Mulched Beds in Rocky Soils of Miami-Dade County - David W. Studstill; Eric H. Simonne; Teresa Olczyk; Rafael Muñoz-Carpena (EDIS, 2006)
HS-1059, a 6-page fact sheet by David Studstill, Eric Simonne, Teresa Olczyk, Rafael-Munoz Carpena, presents the results of a study of flow rates on calcareous soils using dyes to observe the movement of water in the beds under various flow rates and emitter spacings. Published by the UF Horticultural Sciences Department, March 2006.